(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
The anisian succession exposed in the Piz da Peres area, studied by De Zanche et al. (1992) using sequence stratigraphy, is here examined from a micropaleontological point of view. The Recoaro Limestone, deposited during highstand time, contains the most diversified microfauna of the stratigraphic succession; it is Pelsonian in age, with the rypical association Meandrospira dinarica-Pilammina densa; the coeval Pelsonian foraminifers Paulbronnimannia judicariensis (Premoli Silva, 1971) and Paulbronnimannia whittakeri Rettori gen. n., sp. n, are also present.